Scientific research in the learning process for teaching: education, society and science - Villafranqui Cabanillas, Wendy (2020)
The global pandemic situation has made it clear that the consumption of fake news, the predilection for articles to disseminate science rather than scientific research articles, and the legitimation of social networks as sources of information affect social development and maintain those involved vulnerable, as well as susceptible to misinformation. Thus, the need to train citizens with a research profile, interested in science and familiar with its discourses is imminent. In this paper, through documented research that includes social studies, pedagogical approaches and discursive analysis, it’s intended to reflect on the relationship between the current situation of scientific discourse and education, as consequently, its impact on the development of the society. At the end, a working method is proposed for teacher training entities focused on interaction with scientific research texts